Analysis of Financial Ratios and The Economic Value Added (EVA) Method As a Measurement of Financial Performance to Assess the Health of Banks (Case Study of Banks Registered on The Idx For The 2014-2018 Period) - Farhanah Hasanati (Indonesian Journal of Business Analytics, 2023)
The study aim to determine how the banking financial performance based on the Financial Ratios and Economic Value Added (EVA) methods for the 2014-2018 period. The type of research is descriptive quantitative approach using secondary data obtained from idx.co.ix. The study took samples of banking companies listed on the BEI. The sampling methoos is nonprobability, and the sampling technique used purposiv sampling and 17 samples are obtained. The result of the study showed that the liquidity ratio which waas posited wot a long to deposit ratio from three years in a row showed good value. Solvability ratio calculation result which are proxied by the primary ratio show the results above the primary ratio value. The result of the calculation of probability ratios which are proxied by returnon asset and return on equity then to fluctuate. The result of the calculation of ecomonic value added produce economic added value for shareholders.